Rare Skeletal Complications in the Setting of Primary Hyperparathyroidism - Nikos Sabanis; Eleni Gavriilaki; Eleni Paschou; Asterios Kalaitzoglou; Dimitrios Papanikolaou; Pinelopi Ioannidou; Sotirios Vasileiou (Case Reports in Endocrinology)
Parathyroid carcinoma represents an extremely rare neoplasm with diverse clinical manifestations which vary from asymptomatic patients to severe complications of hypercalcemia or parathyrotoxicosis while skeletal involvement is rather common. Herein we aimed at presenting a unique case of a young patient with rare aggressive skeletal complications of parathyroid cancer that initially were misdiagnosed. Ossification of the cervical ligamentum flavum and skull tumor illustrates erosive bonny lesions of hyperparathyroidism that in association with previous medical history of recurrent nephrolithiasis and biochemical findings guide the diagnosis. We suggest that increased awareness and holistic approach are needed in order to recognize and further investigate signs and symptoms of hyperparathyroidism.